Cyber bullying and its impact on mental health among EPJJ students In Universiti Teknologi MARA (UiTM) Kampus Samarahan 2 / Abang Hamizan Abang Mohamad - Abang Mohamad, Abang Hamizan (2023)
Cyberbullying is bullying, but online. It is bullying with the use of digital technologies. It takes place on social media, messages, games and also phones. It repeats a lot which aims to scar, anger and shame the target. It can include stuffsuch as spreading misinformation and lies about the target as well as posting bad and embarrassing photos ofthem on social media just to make fun of them. Cyberbullying can also include sending hurtful, abusive or bad messages on message platforms. Also cyberbullying can be done by making fake accounts to send mean messages to people. Compared to real life bullying, cyberbullying leaves a digital footprint which can be proved useful as evidence for necessary actions to be taken.